Trend analysis of water quality variation of the Karun River using the Mann-Kendall test and geographic information system (GIS) - mohammad reza ansari; ashkan yusefi (مدل‌سازی و مدیریت آب و خاک, 2024)
Introduction Accurate quantification of environmental trends must consider variation at different temporal scales when ignoring variation at one scale could lead to incorrect conclusions about variation at another scale. Many environmental monitoring programs collect temporally resolved but irregular time series data to quantify trends for regulatory, management, or research purposes. Conducting a study to understand the trends and predict future conditions in hydrological aspects such as river water quality is essential. During the last decades, river water quality monitoring has increased by measuring several water quality parameters. Therefore, the analysis of water quality trends is important in providing information about changes or variations in water quality through time series data .Furthermore, determining the quality status of water resources is necessary to adopt proper policies to prevent and enhance the reduction of water quality. Additionally, based on this information, it is possible to identify the quality of river water and implement protective measures to improve and manage rivers and drainage basins in a more integrated way. In recent years, the water quality of the Karun River has been affected by various pollutants, including agricultural runoff and industrial wastewater; Therefore, it seems necessary to monitor the quality of the river and the process of its changes over time and place to know the current situation and provide the necessary measures in the future. Therefore, this research analyzed the Karun River's water quality trend over 20 years at four water quality monitoring stations. Materials and methodsTo check the quality of river water in hydrometric stations, the obtained data were assessed from physical and chemical parameters, including Total Dissolved Solids (TDS), Electrical Conductivity (EC), Sodium adsorption ratio (SAR), Na, and Cl in 20 years from 1998 to 2017 in four hydrometric stations including Gotvand, Shushtar, Mollasani, and Ahvaz of Karun river in the wet season (first six months of the water year) and dry season (the second half of the water year). The process of river water quality and inspecting the changes were conducted using the Mann-Kendall test and a geographic information system, respectively. Wilcox's classification was used to check the water quality from an agricultural point of view, as there are relevant standards. By putting the sodium absorption ratio against salinity, Wilcox presents a chart for the water quality assessment for agricultural purposes and can classify water into different classes based on EC and SAR values. Results and DiscussionAccording to the results, the river water salinity in the wet season in three hydrometric stations significantly increased. The increment was at the level of 10% at the Shushtar and Mollasani stations. However, at the Ahvaz station, it rose to the level of five percent. Due to the different annual rainfall amounts during the study period, the river water’s electrical conductivity had relatively large fluctuations in all the investigated stations. The range of electrical conductivity (EC) alterations in the wet season was between 490 and 2800 µS/cm and in the dry season between 397 and 2806 µS/cm. TDS increased in the wet and dry seasons. Moreover, the p-value showed that the value of this statistic was significant at the level of 10% in the Shushtar and Mollasani stations and at the level of five percent in the Ahvaz station. The range of changes in the wet period was between 250 and 1750 mg/liter and in the dry period between 220 and 1700 mg/liter. The alterations in total dissolved solids were more in the wet than in the dry season and did not have a uniform trend. In fact, the decrease or increase in the amount of precipitation affected the intensity and weakness of the TDS amount during the year. ConclusionThe results of the Mann-Kendall test showed that the parameters of TDS, SAR, Na, Cl, and EC increased during the last twenty years, indicating the expansion of the entry of sewage and industrial and agricultural effluents. According to the Wilcox index, water quality for agricultural purposes was in the average category in all the studied stations. Meanwhile, Na, Cl, and TDS parameters were in the average and inappropriate range in some years, being an alarm regarding the low water quality. Additionally, there is a risk of water quality decline in the investigated stations. In general, the watershed of the Karun River is noteworthy due to the presence of a large population, cities, and centers. Specifically, the city of Ahvaz and the heavy steel industries located in this watershed are important fundamental in terms of water consumption and producing pollutants affecting the quality of water resources, which faces many quantitative and qualitative challenges in water. The study of the changes in the water quality parameters of the stations located in the Karun River during the study period demonstrated that the amount of dissolved salts in these rivers increased and caused the reduction of water quality due to incorrect utilization and failure to comply with the principles of river exploitation.